Fracture penis: what can surgery do? (Bangladesh Journal of Urology, 2012)
Introduction: The purpose of this retrospective study was to review the effect of early surgical exploration and repair of penile fractures. Methods: The participants were 16 patients with a fractured penile shaft following blunt trauma to the erect penis. Data were gathered over a period of 36 months. All patients were treated by surgical repair. Results: Associated urethral injuries were found in 3 out of the 16 patients (18.75%). These patients had bleeding from the urethra at presentation. Seven patients had tears in the tunica albuginea only; the 9 remaining patients also had disruption of the corpus cavernosum. All tears involved the distal two-thirds of the penile shaft. All patients reported normal psychogenic, reflexogenic, and nocturnal erections with full sexual activity at 3- month and 6-month evaluations after surgery. Results of pharmacocavernosometric testing showed that all patients had rigid erections that occurred within 3-10 minutes and lasted for more than 30 minutes. Conclusion: Early surgical exploration and repair of penile fractures gives successful healing of tunical breach, early return to full sexual activity and alleviates risk of venous leak and thereby minimize the incidence of erectile dysfunction as a long-term complication.BJU 2010; 13(1): 10-13